1991
DOI: 10.1111/1467-9566.ep11340787
|View full text |Cite
|
Sign up to set email alerts
|

‘Falling out of culture’: the effects of repetition strain injury on sufferers’ roles and identity

Abstract: Re|:)etition Strain Injury (RSI), a non-specific and controversial constellation of work-related hand, arm and neck symptoms, became endemic in Australian industry in the early 1980s. Fifty two women who worked in a telecommunications organisation and chicken processing factory and had been diagnosed as having Repetition Strain Injury were interviewed about their perceptions and experiences of the illness. Their accounts ofthe effects of the pain and limitation on their work, home lives and identity reveal per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…In addition to financial stress, workplace injury may have negative effects on family relationships [Feuerstein et al, 1985;Ewan et al, 1991;Dawson, 1994;Morse et al, 1998;Keogh et al, 2000;Ballantyne, 2001;Adams et al, 2002;Strunin and Boden, 2004]. For example, data from the US National Longitudinal Survey indicated that workers who experienced a workplace injury were 25% more likely to divorce than the non-injured population [Dembe, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to financial stress, workplace injury may have negative effects on family relationships [Feuerstein et al, 1985;Ewan et al, 1991;Dawson, 1994;Morse et al, 1998;Keogh et al, 2000;Ballantyne, 2001;Adams et al, 2002;Strunin and Boden, 2004]. For example, data from the US National Longitudinal Survey indicated that workers who experienced a workplace injury were 25% more likely to divorce than the non-injured population [Dembe, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on women show that some workers tend to have to search for recognition of their symptoms [Reid et al, 1990. RSI may severely disrupt day-today work and home life as Ewan et al [1991] document in their study of women.…”
Section: Introductionmentioning
confidence: 99%
“…Ewan et al. (1991) wrote about powerlessness in a situation in which patients struggled to convince physicians that their pain was genuine, and described the specialist's approach to patients as ‘overpowering’.…”
Section: The Body In Interaction With the Medical Encountermentioning
confidence: 99%